Pharmacological characterization of muscarinic receptors in dog isolated ciliary and urinary bladder smooth muscle - Choppin, A (2001)
1. The pharmacological characteristics of muscarinic receptors mediating contraction of dog isolated ciliary muscle were determined and compared to those mediating contraction of dog urinary bladder smooth muscle. 2. (+)-Cis-dioxolane induced concentration-dependent contractions of ciliary muscle (pEC(50)=7.18±0.07, E(max)=453±64 mg, n=19) and urinary bladder isolated smooth muscle (pEC(50)=6.55±0.07, E(max)=11±1 g, n=19). These responses were antagonized by several muscarinic receptor antagonists (pK(b) values for the ciliary muscle and the bladder smooth muscle, respectively): atropine (8.25±0.14 and 9.21±0.09), pirenzepine (6.31±0.13 and 6.70±0.25), tolterodine (7.97±0.14 and 8.68±0.12), oxybutynin (7.40±0.08 and 7.88±0.12), zamifenacin (6.46±0.19 and 7.69±0.11), S-secoverine (6.66±0.14 and 8.13±0.07), AQ-RA 741 (6.16±0.15 and 7.08±0.23), p-F-HHSiD (7.10±0.27 and 7.35±0.07) and responses were not antagonized by PD 102807 (up to 100 nM). 3. In urinary bladder smooth muscle, the profile of antagonist pK(B) values correlated significantly with pK(i) values at human recombinant m(3) muscarinic receptors, suggesting that M(3) muscarinic receptors mediated the response. In the ciliary muscle, a significant (P<0.01) correlation was obtained with human recombinant m(3) and m(5) receptors. 4. Darifenacin displayed insurmountable antagonism at receptors in the bladder. At receptors in the ciliary muscle, it exhibited two phases of antagonism, comprising an initial low affinity (pK(B)<6) component and a high affinity phase (pK(B)>8). 5. The role of pigmentation in the atypical behaviour of darifenacin was examined. In blue coloured eyes, darifenacin produced apparent surmountable, competitive antagonism of the responses to (+)-cis-dioxolane (pK(B)=8.76±0.07). The antagonist profile obtained in this tissue suggested the involvement of a site which has the pharmacological attributes of the M(5) receptor. 6. We suggest that the dog urinary bladder contracts in response to M(3) muscarinic receptor activation. Contraction of the brown-eyed dog ciliary muscle is more complex and may include involvement of at least two receptors, possibly the M(5) and M(3) receptor, whereas blue-eyed dog ciliary muscle may involve a single population of M(5) muscarinic receptors.